Long-term Outcome of Chilblains Associated with SARS-CoV-2 - Florence Poizeau; Sébastien Barbarot; Yannick Le Corre; Emilie Brenaut; Mahtab Samimi; Hélène Aubert; Alexis Toubel; Alain Dupuy (Medical Journals Sweden, 2021)
Numerous cases of chilblains have been observed in the course if the COVID-19 pandemic. The aims of this study were to provide comprehensive follow-up data for patients reporting chilblains, and to determine the risk factors for incomplete recovery. Patients referred to 5 hospitals in France between March and May 2020 for chilblains were surveyed on December 2020. A teleconsultation was offered. Among 82 patients reporting chilblains, 27 (33%) reported complete recovery, 33 (40%) had recurrences of chilblains after their hands and feet had returned to normal, and 22 (27%) developed persistent acral manifestations, mostly acrocyanosis, with or without further recurrences of chilblains. Most recurrences of chilblains occurred during the following autumn and winter. A past history of chilblains was not associated with recurrences or persistent acral manifestations. Women had a significantly higher risk of developing recurrences or persistent acral manifestations (odds ratio 1.30; 95% confidence interval 1.06-1.59). In conclusion, two-thirds of patients reporting chilblains at the start of the COVID-19 pandemic experienced persistent or recurrent acral manifestations after a 10-month follow-up.